Whither Proxies II? - Švob, Goran (2005)
The notion of possible worlds was introduced into philosophical analysis as an eliminable theoretical term. However, in contemporary discussions it often, undeservingly figures as an indispensable and intuitively clear primitive term. Together with set-theoretically defined notion of identity it presents a fundamental problem in the foundation of contemporary philosophical logic.